Finance and Development, September 2014. (Finance and Development; Finance and Development, 2014)
This chapter discusses various past and future aspects of the global economy. There has been a huge transformation of the global economy in the last several years. Articles on the future of energy in the global economy by Jeffrey Ball and on measuring inequality by Jonathan Ostry and Andrew Berg are also illustrated. Since the 2008 global crisis, global economists must change the way they look at the world.